2020
DOI: 10.1021/acs.analchem.0c02133
|View full text |Cite
|
Sign up to set email alerts
|

Higher Resolution Charge Detection Mass Spectrometry

Abstract: Charge detection mass spectrometry is a single particle technique where the masses of individual ions are determined from simultaneous measurements of each ion’s m/z ratio and charge. The ions pass through a conducting cylinder, and the charge induced on the cylinder is detected. The cylinder is usually placed inside an electrostatic linear ion trap so that the ions oscillate back and forth through the cylinder. The resulting time domain signal is analyzed by fast Fourier transformation; the oscillation freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 74 publications
4
80
0
Order By: Relevance
“…As such, this approach can overcome the challenges for analyzing highly heterogeneous biomolecular assemblies, for which—when measured by conventional native MS—individual charge states are often indistinguishable or extremely broadened, hampering accurate mass determination. Conventional CDMS approaches, including single-pass detection cylinder(s) and multi-pass ion trap-based detectors ( Keifer et al., 2017 ), exist already for several decades and have been successfully applied to studying of various biomolecules and polymers in the wide mass ranges ( Antoine, 2020 ; Keifer and Jarrold, 2017 ; Todd et al., 2020 ). Recently, the quantification and the appropriate calibration of induction image current for individual ions have enabled charge determination of single particles on commercially available Orbitrap mass analyzers ( Kafader et al., 2020b ; Wörner et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, this approach can overcome the challenges for analyzing highly heterogeneous biomolecular assemblies, for which—when measured by conventional native MS—individual charge states are often indistinguishable or extremely broadened, hampering accurate mass determination. Conventional CDMS approaches, including single-pass detection cylinder(s) and multi-pass ion trap-based detectors ( Keifer et al., 2017 ), exist already for several decades and have been successfully applied to studying of various biomolecules and polymers in the wide mass ranges ( Antoine, 2020 ; Keifer and Jarrold, 2017 ; Todd et al., 2020 ). Recently, the quantification and the appropriate calibration of induction image current for individual ions have enabled charge determination of single particles on commercially available Orbitrap mass analyzers ( Kafader et al., 2020b ; Wörner et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent innovations have revealed that CDMS can resolve the difference between a filled and unfilled capsid of a virus. [24]. The possible presence of a small amount of non-microbe material is not expected to affect morphological identification or chemical identification of a pathogen.…”
Section: Methodsmentioning
confidence: 99%
“…The larger deviations (from the theoretical square root behavior) for the actual single ion intensities compared to the noise band suggest additional artifacts, rather associated with ion behavior than pure instrument performance. Beside sample heterogeneity in the HBV capsid assemblies 36 , these artifacts are most likely caused by the wide range of kinetic energies accepted by the Orbitrap as well as eccentric, non-circular orbits, both impacting the radial distance and thus the induced image current 37 .…”
Section: Optimizing Orbitrap-based Charge Detection Mass Spectrometry Of Megadalton Particlesmentioning
confidence: 99%